MULTI DISCIPLINE COLLABORATION BETWEEN ART AND TECHNOLOGY ON APPLYING VERTICAL CROSS CONFIGURATION FOR MAKING AESTHETIC BOARD - Firman Hawari; Agus Sachari; Adhi Nugraha; Dicky Rezaldy Munaf (Universitas Sebelas Maret, 2017)
The stimulus in this study is to reduce dependence on natural resources, in this case timber, and preserve it from extinction. It is based on comparison between high utilization rate and imbalance with its availability. Field observations indicate that large utilization of wood is for making as a board. The condition raises motivation to find alternative creation of boards from non-timber materials, in this case urban waste. Various ideas, thoughts and applications are experimented to get best methods to produce board products from municipal waste as per required and feasible qualifications. After several stages of research and experimentation, a method called vertical cross configuration was obtained. In some advanced applications, this configuration has been able to help produce a strong, sturdy, and aesthetic board products.The following study directs systematic thinking of identifying multi-disciplinary collaboration, in this case technology and aesthetics, on creation activities of vertical cross-configuration through utilization of municipal waste as raw materials. The discussion covers definition of vertical cross-configuration, discipline of science involved, interdisciplinary collaboration, resulting product and its utilization opportunities. Understanding of this study is expected to encourage people involved in the production process and application of aesthetic board utilization to take an active role in environmental conservation in a wider scope.